Mukositis Oral pada Pasien Kanker Rektum yang Menjalani Kemoterapi: Laporan Kasus - Resmaputri, Ayu Meitri; Triani, Maulina; Rahmah, Hanny Aulia (Jurusan Kedokteran Gigi Fakultas Kedoketaran Universitas Jenderal Soedirman, 2025)
Background: Chemotherapy is a cancer therapy modality that uses high-energy ionizing radiation rays. One of the effects of chemotherapy on the oral cavity is that it can increase the occurrence of opportunistic infections such as oral mucositis. Purpose: The purpose of this publication is to report the findings of oral mucositis in rectal cancer patients undergoing chemotherapy. Case: A 45-year-old female patient complained of sore lips and mouth two weeks ago. The patient has a history of rectal cancer and anemia and was treated in the internal disease inpatient ward at RSUD Prof. Dr. Margono Soekarjo, this patient has undergone chemotherapy procedures three times and blood transfusion treatment. Case Management: The treatment plan that can be given is in the form of pharmacological therapy by administering benzydamine HCl mouthwash, chlorhexidine gluconate, vitamin B12, and folic acid. Non-pharmacological therapy in the form of communication, information and education is given to patients to avoid several predisposing factors and requires collaboration with specialist doctors who are treating systemic diseases. In this case, the patient is given non-pharmacological therapy. Conclusion: The principles of managing oral mucositis include administering mouthwash that varies based on the severity of the oral mucositis and supportive therapy with vitamin B12 and folic acid.